(untitled) - Wilkins, Roy; Mathews, Tom (New York, 1982)
Includes index; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Wilkins, Roy, -- 1901-; United States -- Race relations; Hoa Kỳ -- Quan hệ chủng tộc; African Americans -- Civil rights; African Americans -- Biography; Người Mỹ gốc Phi -- Dân quyền